Product Development And Performance of Reinforced Metal Matrix Composite Brake Disc: Modelling, Simulation And Multi-Criteria Decision Making Technique - Nanang Fatchurrohman; Gan Wei Kang; Muhammad Ilham Adelino (Spektrum Industri, 2021)
Demand for lightweight and durable components for automotive applications is increasing, such as brake discs. This paper presents an investigation on new material for brake discs which is metal matrix composite (MMC). This new material offers high strength â€“ lightweight performance and high thermal conductivity if applied to automotive brake discs. This paper also explores new designs for brake disc using MMC as the material. The objective of this study is to present a recommendation for new brake disc material and design which can replace the existing one in terms of higher braking performance. Modelling, simulation, and multi-criteria decision making (MCDM) technique were used toselect the best design of MMC brake disc. The results show that Design 6 (with angular grooves) has the best performance at dissipating heat, reaching the highest temperature of 284.66Â°C and it has the lowest deformation of 0.589 mm. Subsequent analysis using MCDM shows that Deign 6 has the highest normalised priority of 0.2742 or the best alternative. The combination of MMC as the new material and new design can improve thermal and structural performance, hence improving the vehicle braking performance.